Peningkatan Kemampuan Komunikasi Matematis Siswa Menggunakan Model Problem Based Learning Kelas VIII SMP N 1 Bandar - Mariani Sitanggang (Universitas Islam Sumatera Utara, 2022)
With the help of the problem-based learning methodology applied to block content in class VIII SMP N 1 Bandar, the goal of this study is to ascertain if students' mathematical communication abilities have improved. Students in class VIII at SMP N 1 Bandar served as the research participants, and the problem-based learning paradigm was the study's focus. With a sample of 27 students in class VIII-4 SMP, classroom action research (CAR) was the methodology used. The block's surface area and volume were assessed during two cycles of this study's execution. In cycle I, there were 8 students who finished their education with a completion rate of 29.62%, while there were 19 students who did not, with a completion rate of 70.37%. Â Students who passed cycle II had 21 students with a percentage of 77.78%, whereas those who had not finished had 6 students with a percentage of 22.22%. These students had improved their mathematical learning outcomes on the surface area and volume of blocks. Thus, it may be argued that the entire class can be considered finished.